1976
DOI: 10.1177/028418517601700615
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Measurements on the Radio-Carpal Joint in Distal Radial Fractures

Abstract: Radiography of 40 wrists with fractures in the distal part of radius was performed. In the lateral view the inclination of the radial joint surface was analysed in different degrees of pronation and supination. The central ray was directed 15 degrees proximally and the results were compared with those obtained with a perpendicular central ray. In the perpendicular projections even moderate differences in pronation or supination between two examinations could seriously alter the measured inclination of the join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 3 publications
2
14
0
Order By: Relevance
“…Observer variability in measurement of distal radius angles has been addressed in two previous studies [1,2]. Friberg and Lundstrom [2] measured radial angle and palmar tilt on 60 normal radiographs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Observer variability in measurement of distal radius angles has been addressed in two previous studies [1,2]. Friberg and Lundstrom [2] measured radial angle and palmar tilt on 60 normal radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…A lateral radiograph with the X-ray beam directed 15 ~ cephalad was also made (Fig. 1) [2,3]. Radiographs were randomly labeled so observers could not tell which, if any, were related.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1,2] However, the morphometric interpretation of the wrist bone anatomy is dependent on the quality of the appearance and location of the bony landmarks which is significantly influenced by the positioning of the arm, forearm and wrist in relation to the x-ray beam. [3][4][5][6] The significant morphological variations observed at the wrist joint are certainly factors that could result in wrist abnormalities. [4,5] Gilula and Chesaru measured the scapholunate angle and reported that 30-60° was normal, [7] while 60-80° was questionably abnormal, and >80° out-rightly abnormal and the capitolunate angle of <30° was normal.…”
Section: Introductionmentioning
confidence: 99%